ANALISIS IMPLEMENTASI KEBIJAKAN PENDIDIKAN BERKUALITAS DALAM MENDUKUNG PENCAPAIAN SDGS 4 di KOTA SURABAYA - Ahmad Fahronil Musthofa; Muhammad Kholaf Abiyyu Farros; Indah Prabawati; Firre An Suprapto (Jurnal Manajemen Pendidikan, 2026)
This research tends to analyze the implementation of quality education policy to assist the Sustainable Development Goals (SDGs) achievement, especially the fourth goal, in the city of Surabaya. This research implements a descriptive qualitative approach with a literature research method that utilizes various data sources, such as scientific journals, policy documents, and previous research results. The outcomes show that the inclusive education policy’s implementation in Surabaya city has had a positive impact on increasing access to education, especially for students with special needs. This condition is supported by various programs, including the development of inclusive schools, the stipulation of educational infrastructure and facilities, and improving the competence of teaching staff. However, the implementation policy still meets several obstacles, like the limited number of special assistant teachers, the uneven distribution of educational facilities, and an evaluation system that has not been optimally implemented. Based on policy implementation theory, the success of these policies is affected by factors namely resources, communication, bureaucratic structure, and disposition. Therefore, several attempts are required to strengthen coordination between stakeholders, enhance the quality of human resources, and optimize the evaluation system to assist the achievement of SDGs 4 in a sustainable manner.